Implementation of Brazil's National Policy on Complementary and Integrative Practices: strengths and weaknesses - Leonetti Habimorad, Pedro Henrique [UNESP]; Catarucci, Fernanda Martin [UNESP]; Talarico Bruno, Vania Hercilia [UNESP]; Silva, Ivan Beteto da [UNESP]; Fernandes, Violeta Campolina [UNESP]; Piva Demarzo, Marcelo Marcos; Spagnuolo, Regina Stella [UNESP]; Patricio, Karina Pavao [UNESP] (Abrasco-assoc Brasileira Pos-graduacao & Saude Coletiva, 2020)
This narrative review examines the literature on complementary and integrative practices (CIPs) and their incorporation into Brazil's national health system (Sistema Unico de Sande - SUS) in an attempt to understand the strengths and weaknesses of the implementation of the National Policy on Complementary and Integrative Practices in the SUS (PNPIC, acronym in Portuguese). A search was conducted of the MEDLINE, LILACS, and SciELO databases, resulting in final sample of 25 articles. Our analysis identified five key themes in the literature related to the strengths and weaknesses of policy implementation: 1) Professional training in CIPs in the SUS; 2) structuring the provision of CIPs, access, and health promotion; 3) knowledge, access, and acceptance of service users in relation to CIPs; 4) knowledge of SUS professional staff and managers in relation to the PNPIC; and 5) scope and monitoring and evaluation of the PNPIC. In consonance with the conclusions of the PNPIC management reports, the findings provide a deeper insight into policy implementation problems and reinforce the need to empower the actors involved in this process to tackle these challenges.
Keywords: Review; Complementary Therapies; Unified Health System; Public Policy